2022
DOI: 10.3389/fpsyt.2022.957382
|View full text |Cite
|
Sign up to set email alerts
|

Association of social support with negative emotions among Chinese adolescents during Omicron-related lockdown of Shenzhen City: The roles of rumination and sleep quality

Abstract: ObjectiveAdolescents are likely to suffer from negative emotions such as depression and anxiety due to the rapid development of biological, cognitive and social changes. Previous studies have indicated possible risk (rumination) and protective (good social support and high sleep quality) factors for depression and anxiety among this age group. The present study is the first to investigate the association between social support and negative emotions during the Outbreak of Omicron variant, on this basis, to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Cavalcanti et al also found that clinical depression is a vital risk factor for poor sleep quality [35]. Moreover, Guo et al suggested that sleep problems were more prevalent among adolescents with depressive symptoms [33]. Loneliness can signi cantly effect sleep quality in adolescents with MADD.…”
Section: Variablesmentioning
confidence: 99%
“…Cavalcanti et al also found that clinical depression is a vital risk factor for poor sleep quality [35]. Moreover, Guo et al suggested that sleep problems were more prevalent among adolescents with depressive symptoms [33]. Loneliness can signi cantly effect sleep quality in adolescents with MADD.…”
Section: Variablesmentioning
confidence: 99%
“…Social support is defined as the physical, cognitive and emotional support that individuals in society use social network relationships to get (Gottlieb & Bergen, 2010). Social support considerably impacts physical and mental health and has been identified as an important protective factor against negative emotional states (Guo et al, 2022;Yu et al, 2020). Studies have consistently shown that social support can help individuals reduce the impact of stressors on themselves and play an essential role in regulating individual mental health (Al-Dwaikat et al, 2022;Ning et al, 2022;Sufredini et al, 2022;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the prevalence of PEs in college students is 16% in the U.S. [7], 24% in the United Kingdom, 13% in China, and 20% in Japan [6]. PEs are common in adolescence, often co-occur with mental disorders [8][9][10][11], and may increase the risk of depression, anxiety, and substance abuse during adolescence [12][13][14], and of psychosis later in life [15]. Some studies have found that PEs are correlated with various factors, such as sex, age, and mental health (depression, stress, and anxiety) [6,16].…”
Section: Introductionmentioning
confidence: 99%